Clinical characteristics and outcomes of 85 intensive care patients with Covid-19 in South London: A single centre observational study. (February 2022) - Isted, Alexander; McDonnell, Angus J; Jones, Eben; Grundy, Tomas; Jeyabraba, Swarna; Ali, Tariq O; Khorasanee, Reza; Bhalla, Aditya; Shurovi, Badrun; Rowland, Katie; Sykes, Richard; Yoon, Soo; et al.
Background: In March 2020, Covid-19 secondary to Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) was declared a global pandemic. Methods: This retrospective observational study included patients with Covid-19, managed in a single intensive care unit (ICU). We collected data on patient characteristics, laboratory and radiological findings and ICU management. Data are reported as median (interquartile range). Binary logistic regression modelling was used to identify variables at ICU admission associated with mortality. Results: 85 patients (age 57.3 years [49.4–64.2], 75.3% male) were followed up for 34 days (26–40). The commonest comorbidities were hypertension (51.8%), obesity (48.7%), and type 2 diabetes (31.8%). Covid-19 presented with shortness of breath (89.4%), fever (82.4%), and cough (81.2%), first noted 8 days (6–10) prior to ICU admission. PaO2 /FiO2 -ratios at ICU admission were 8.28 kPa (7.04–11.7). Bilateral infiltrates on chest X-ray, lymphopenia, and raised C-reactive protein and ferritin were typical. 81.2% received invasive mechanical ventilation (IMV). Acute kidney injury occurred in 62.4% with renal replacement therapy required in 20.0%. By the end of the follow-up period, 44.7% had died, 30.6% had been discharged from hospital, 14.1% had been discharged from ICU but remained in hospital and 10.6% remained in ICU. ICU length of stay was 14 days (9–23). Age was the only variable at admission which was associated with mortality. PaO2 /FiO2 -ratio, driving pressure and peak ferritin and neutrophil count over the first 72-hours of IMV all correlated with mortality. Conclusions: We report the clinical characteristics, ICU practices and outcomes of a South London cohort with Covid-19, and have identified factors which correlate with mortality. By sharing our insight, we hope to further understanding of this novel disease.